2008
DOI: 10.1155/2008/982341
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Charmonium and the ρπ Puzzle

Abstract: Using the method of QCD sum rules, we estimate the energy of the lowest hybrid charmonium state, and find it to be at the energy of theΨ′(2S) state, about 600 MeV above theJ/Ψ(1S)state. Since our solution is not consistent with a pure hybrid at this energy, we conclude that theΨ′(2S) state is probably an admixedcc¯and hybridcc¯gstate. From this conjecture, we find a possible explanation of the famousρ−πpuzzle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 19 publications
2
29
1
Order By: Relevance
“…In former studies [16,18], people also fought the same target but with some differences from this work. In previous works, operator expansion only up to dimension four, but in our study the dimension six operators are taken into account.…”
Section: Discussionmentioning
confidence: 95%
“…In former studies [16,18], people also fought the same target but with some differences from this work. In previous works, operator expansion only up to dimension four, but in our study the dimension six operators are taken into account.…”
Section: Discussionmentioning
confidence: 95%
“…The vector component provides a separate sum rule, but the sum rule with the scalar component has less error (as determined from the method of QCD sum rules in previous calculations-see, e.g., Refs [5,4]). From Eq(7) we obtain…”
Section: σ and 2π Decays Of The ψ ′ (2s)mentioning
confidence: 99%
“…For the Υ(nS) states this provides an explanation for the unusual two-pion decays [6]; and for the Ψ ′ (2S) this solves the famous ρ − π problem. Prior to this, we had studied the Ψ ′ (2S), also using the method of QCD sum rules, and found [5] that it was not a pure hybrid. In the present work we estimate the decay of the Ψ ′ (2S) to the J/Ψ(1S) with a sigma or two free pions as a test of our mixed heavy quark hybrid meson theory.…”
mentioning
confidence: 99%
“…This solves many puzzles [4,5]. In Ref [3] it was found that the ratios of cross sections, with the σ a broad 2-pion resonance,…”
Section: Introductionmentioning
confidence: 99%